Strategic Leadership and Artificial Intelligence Integration in the Pharmaceutical Industry - Dwivedi, Charuta (Digital Repository of Theses, 2026)
Purpose: The traditional leadership practice emphasises operational execution, yet strategic leadership offer long-term vision and adaptability. It is necessary to support the vision of this industry and enhance its expansion towards the global market. The key purpose of this research is to identify the effectiveness of strategic leadership to support the effective implication of AI technologies in pharmaceuticals. It creates a huge scope for this study to set a base for further research on similar topics. An AI system reinforces existing prejudices if the data is not representative of the population it serves. Methodology: Mixed methods are used in this research, which involves both qualitative and quantitative information. The survey method is used to collect quantitative information from primary research practices. 200 participants are included in the present study, and these individuals are selected through purposive sampling, and the data are further analysed through Excel. Existing literatures are used to collect secondary qualitative information from authentic sources. The secondary data is further emphasised through the thematic analysis. Findings: The findings of mixed data analysis illustrate that the healthcare provider must anticipate upcoming trends, carefully thought-out and manage changes to ensure long-term decisions and organisational targets contribute to the growth of the health sector. These leaders allow to lead organisations to handle unpredictable situations in markets, while sponsoring an environment where information, people and ideas are evaluated. The finding also emphasises that strategic leadership is associated with responsibilities of engaging development for implementing ongoing change and building skills in accordance with a complex and competitive environment. This trend of changing different pharmaceutical organisations operates in collaboration with companies and institutions, incorporating AI in product development. Conclusion: In conclusion, the study found that AI integration and strategic leadership are linked to the trend of digital transformation and the apparent emergence of leadership competency, with AI technology being implemented as digital advancements for maintaining competence among pharmaceutical industry. The findings of study revealed that leadership has a significant influence in the integrated adoption of AI within the pharmaceutical sector as a culture, as well as innovative integration into the organization's operations and workforce culture. Keywords: AI, digital transformation, pharmaceutical industry, strategic leadership, development, competence.